Pengembangan Video Pembelajaran Tari Indang pada Mupel SBdP Kelas VI di Sekolah Dasar - Nana Prasetya Ayuni; Wawan Priyanto; Mei Fita Asri Untari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The background of the research is the lack of interest of students in learning the art of dance, the limited expertise of teachers and the lack of school facilities. The main object of this research is to determine the characteristics, validity, and practical elements of developing video learning by using "The Research and Development" method. The subjects of the research were students and teachers at SD N 1 Tawangharjo and SD N 3 Sambirejo. The analysis technique to test the validity of the product is validated by media experts and material experts. Based on the validation test results by media experts and material experts, the percentages of results are 98% for the media and 95% for the material. Referring to the validation results, the development of Indang dance learning videos on the content of the SBdP class VI subject matter on theme and sub-theme 2 for the 2nd lesson in elementary school is very valid and feasible to use without revision.